2018
DOI: 10.5194/acp-2018-63
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for pyrazine-based chromophores in cloudwater mimics containing methylglyoxal and ammonium sulfate

Abstract: Abstract. Simulating aqueous brown carbon (aqBrC) formation from small molecule amines and aldehydes in cloud water mimics provides insight into potential humic-like substance (HULIS) contributors and their effect on local and global aerosol radiative forcing. Previous work has shown that these (Maillard type) reactions generate products that are chemically, physically, and optically similar to atmospheric HULIS in many significant ways, including in their complexity. Despite numerous characterization studies,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Upon exposure to UV radiation, however, masses at m / z 83 and 97 are observed to increase dramatically in magnitude when irradiated (150 and 230%, respectively); these peaks are attributable to methylimidazole and dimethylimidazole, both of which have been observed in MG/AS dark-chemistry reaction systems (Table ). ,, While not particularly light-absorbing in the 280 nm region, these aqSOA products notably share the common quality of containing a relatively small, polar overall structure (imidazole) with nonpolar methyl groups. Because this trait is similar to MG itself, which acts as a surfactant even in the absence of other chemistry, this may be sufficient to enable these molecules to partition to gas–droplet surfaces or persist at the interface upon formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon exposure to UV radiation, however, masses at m / z 83 and 97 are observed to increase dramatically in magnitude when irradiated (150 and 230%, respectively); these peaks are attributable to methylimidazole and dimethylimidazole, both of which have been observed in MG/AS dark-chemistry reaction systems (Table ). ,, While not particularly light-absorbing in the 280 nm region, these aqSOA products notably share the common quality of containing a relatively small, polar overall structure (imidazole) with nonpolar methyl groups. Because this trait is similar to MG itself, which acts as a surfactant even in the absence of other chemistry, this may be sufficient to enable these molecules to partition to gas–droplet surfaces or persist at the interface upon formation.…”
Section: Resultsmentioning
confidence: 99%
“…4,17−19 These reactions can range from selfoligomerization processes to reactions with inorganic components, such as ammonium ions that are also present within the aqueous phase. 17,20−24 Resulting nitrogen-containing products, such as pyrazine 25 or imidazole 26,27 derivatives, also retain some oligomeric behavior in their own right, continuing to take on additional dicarbonyl units as they continue to age. MG and its dark-chemistry products have been demonstrated to depress surface tension in aerosol mimic solutions, 20,28 while G and its dark-chemistry products were observed to not be surface-active under similar reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the MG–AS brown carbon system may affect the atmospheric photochemistry in aerosol particles, but with limited impact on the direct radiative forcing of climate. Hawkins et al 8 provided evidence for the pyrazine-based chromophores in cloud-water mimics containing MG and AS, which had implications in the further clarification of the reactivity and degradation pathways of brown carbon. According to the optical properties and chemical composition of individual brown carbon components produced through the reactions of MG and AS, Lin et al 21 found that the reduced-nitrogen organic compounds formed in the reactions between atmospheric carbonyls and ammonia/amines are important brown carbon chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions of carbonyl compounds with ammonia or ammonium to form hemiaminals and imines contribute to the formation of light-absorbing SOA in the atmosphere (De Haan et al, 2011;Hawkins et al, 2018;Lee et al, 2013;Powelson et al, 2014). In this work, we found that acrolein, the smallest α,β-unsaturated aldehyde, has the potential to form light-absorbing heterocyclic NOC, as shown in Figure 9.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%